Intestinal parasites in feral populations of domestic pigeons (Columba livia domestica) in Coro, Falcon State, Venezuela - Cazorla Perfetti, Dalmiro (2019)
The domestic pigeon (Columba livia domestica) is a columbiform bird species well-adapted to anthropic environments. However, it can serve as a carrier of pathogenic microorganisms of zoonotic interest. Between August 2017 and August 2018 feces of feral populations of domestic pigeons were collected to determine the occurrence of intestinal parasites in three sites of the city of Coro, Falcon state, Venezuela: University Hospital "Alfredo Van Grieken", a bus terminal and the National Experimental University "Francisco de Miranda". The samples (n=516) were analyzed by five coprological methods: direct test, Willis-Molloy flotation (ClNa), Faust flotation (zinc sulphate), spontaneous sedimentation in tube and Kinyoun staining. The parasitological analysis revealed the presence of 12 parasitic taxa in 54.3% (280/516) of faecal samples, of which several are considered of medical-zoonotic importance (Cryptosporidium spp, Blastocystis spp, Cyclospora spp). The most prevalent taxa were Criptosporidium spp (38.5%), Isospora spp (19.4%), Cyclospora spp (13%) and Raillietina spp (7.8%). The implications of these findings in the context of public health are discussed.